(untitled) (Communication In Physical Sciences, 2010)
Authors: F. N. Okekel , W. T. Sivla2, S.O. Agha3, and E.A. Hanson4 The study of midlatitude ionospheric storm dynamic low latitude irregularities and equatorial region have shown that the midlatitude is much more dynamic than earlier predicted. It was found that strong enhancement of electron density that occurred in midlatitude at midday, could also favour the local E X B instability that is driven by thermospheric wind. Hence, the high effect of ionospheric disturbances was recorded at the midlatitudes, which was attributed to increase in solar activities. On the other hand, minor storm effect was observed in the equatorial region. It was then concluded that very strong storin effects recorded in the multitudes could be responsible for its being conspicuously very dynamic.